2019
DOI: 10.1097/md.0000000000015469
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dexmedetomidine for treatment of patients with sepsis

Abstract: Background: This meta-analysis aimed to evaluate the effect of dexmedetomidine on prognosis in patients with sepsis. Methods: Computer-related electronic databases were searched, including PubMed, Embase, Web of Science, the Cochrane Library, and the China National Knowledge Infrastructure, from the date of database construction to January 2019. Stata 12.0 was used to perform a meta-analysis of short-term mortality [intensive care unit (ICU) mortality or 28-day mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…The mechanism has been suggested as Dex reducing the release of inflammatory cytokines, such as TNF and IL-6, by inhibiting the activation of ERK1/2 and NF-κB and modulating inflammatory mediators. [39][40][41] Subsequently, Dex could also suppress toll-like receptor 4 signaling, activate the cholinergic anti-inflammatory pathway, and intensify macrophage phagocytosis for bacterial clearance, thus stabilizing hemodynamics. [42][43][44] Acute kidney allograft rejection occurs as a consequence of interactions between recipient immune cells within the transplanted organ as is the cause of 64% of renal transplantation failures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism has been suggested as Dex reducing the release of inflammatory cytokines, such as TNF and IL-6, by inhibiting the activation of ERK1/2 and NF-κB and modulating inflammatory mediators. [39][40][41] Subsequently, Dex could also suppress toll-like receptor 4 signaling, activate the cholinergic anti-inflammatory pathway, and intensify macrophage phagocytosis for bacterial clearance, thus stabilizing hemodynamics. [42][43][44] Acute kidney allograft rejection occurs as a consequence of interactions between recipient immune cells within the transplanted organ as is the cause of 64% of renal transplantation failures.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated reduced risks of infections associated with Dex administration. The mechanism has been suggested as Dex reducing the release of inflammatory cytokines, such as TNF and IL‐6, by inhibiting the activation of ERK1/2 and NF‐κB and modulating inflammatory mediators 39–41 . Subsequently, Dex could also suppress toll‐like receptor 4 signaling, activate the cholinergic anti‐inflammatory pathway, and intensify macrophage phagocytosis for bacterial clearance, thus stabilizing hemodynamics 42–44 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, no significant differences were found in the survival of patients who received dexmedetomidine compared with those who did not. Different data have been reported in this regard in multiple clinical contexts [ 34 , 35 ]: A Cochrane meta-analysis evaluating the impact of dexmedetomidine versus traditional sedatives on mortality in critically ill patients found no significant association between its use and mortality [ 34 ]. On the other hand, a meta-analysis published by Zhang et al, which included eight studies, evaluated the outcomes of patients who received dexmedetomidine in the context of sepsis and found a decrease in ICU mortality in those who received it with respect to those who did not (RR 0.44; 95% CI 0.23–0.84) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, the rapid development of modern biotechnology has dramatically promoted the public understanding of sepsis pathogenesis and the improvement of sepsis treatment ( Harisha, 2014 ). According to a large amount of clinical and experimental research, the data on sepsis treatment and new drug development did not seem to be promising ( Fuchs et al, 2019 ; Zhang et al, 2019 ). Strategies for intervention in sepsis have shown useful application prospects in animal experiments; however, they have not achieved significant clinical efficacy in phase II and phase III clinical trials, and some have even exacerbated the disease ( Schimmer et al, 2016 ; Łysenko et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%